Oral health status in children undergoing chemotherapy at Erbil city: A case control study. - Zahraa Emaad Ahmed; Sazan Sherdl Salim (Erbil Dental Journal)
Background: Chemotherapy is a well-known effective treatment for cancer but is associated with many side effects including that of the dental and oral aspects, which have an impact on the overall/general health-related quality of life. This study aimed to assess oral health status in a specified age group of pediatric patients who were undergoing chemotherapy for acute lymphoblastic leukemia (ALL) at the time of the study as well as identify the factor that indirectly contributes to their OHS and compare the results with healthy children of similar age.